1993
DOI: 10.1007/bf01290341
|View full text |Cite
|
Sign up to set email alerts
|

Pion and fast proton production in $$\bar p$$ A annihilation at rest

Abstract: Abstract. We consider annihilation pions scattering and absorption inside the nucleus to analyse fast proton production in/SA annihilation. The method suggested allows description of both pion and proton spectra, particularly high energy proton tail. New experimental data obtained at LEAR are analysed and we have found an extraordinary behaviour of pion scattering and absorption probabilities depending on atomic number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The solid, dashed and dotted lines show our results calculated with the resonance model. The dashed-dotted line shows (5). Figure 4: The invariant mass spectrum of the π + p system in the reaction pd → pπ + 2π − mπ 0 for protons with momenta above 400 MeV/c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid, dashed and dotted lines show our results calculated with the resonance model. The dashed-dotted line shows (5). Figure 4: The invariant mass spectrum of the π + p system in the reaction pd → pπ + 2π − mπ 0 for protons with momenta above 400 MeV/c.…”
Section: Discussionmentioning
confidence: 99%
“…One of the traditional mechanisms of fast baryon production following the antiproton annihilation is the secondary interactions of the pions as well as the mesonic resonances in the nuclear environment. It was shown by Sibirtsev [5] that the high momentum tail of the proton spectra from carbon and uranium targets can be reproduced with the rescattering and absorption of the annihilation mesons. Fasano et al [6] found that the pion rescattering can explain the fast proton production in the reaction pd → 5πp but strongly underestimates the proton spectrum from reaction pd → 3πp.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies of fast proton production in fil2C and /5238U annihilation at rest [6,7] resulted in two essential conclusions. First, because nucleons already exist inside the nucleus, one needs an energetic projectile to knock them out.…”
Section: Introductionmentioning
confidence: 94%
“…Experimental data on proton production in /512C and /523su annihilation at rest show significant yields of fast protons with energy above ~600 MeV [6]. Although interpretation of these results by means of the two-step process seems reasonable to the first approximation [-7], it was necessary to incorporate a large probability for antiproton absorption on two bound nucleons, or sixquark objects (q6), inside the nucleus to explain the data in detail [6,7].…”
Section: Introductionmentioning
confidence: 98%